2018
DOI: 10.1038/s41419-018-0864-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy increases susceptibility of glioblastoma stem cells to temozolomide by igniting ferroptosis

Abstract: The role of autophagy in cancer onset and progression appears still controversial. On one hand, autophagy allows cancer cell to survive in unfavorable environmental conditions, on the other hand, once internal energy resources are exhausted, it leads to cell death. In addition, autophagy interpheres with cell cycle progression, de facto exerting a cytostatic activity. Hence, it represents an important target for anticancer therapy. For example, temozolomide (TMZ), of use for glioblastoma (GBM) treatment, appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(157 citation statements)
references
References 65 publications
4
151
1
1
Order By: Relevance
“…TMZ selectively induced GSCs to undergo ferroptosis but not apoptosis or necrosis in TMZ‐induced cell death during treatment. That result also showed the sensitivity of ferroptosis induction in brain tumours …”
Section: Main Textmentioning
confidence: 55%
“…TMZ selectively induced GSCs to undergo ferroptosis but not apoptosis or necrosis in TMZ‐induced cell death during treatment. That result also showed the sensitivity of ferroptosis induction in brain tumours …”
Section: Main Textmentioning
confidence: 55%
“…32,33 Autophagy may function either as a cell survival mechanism under specific conditions, or as a second type of programmed cell death. 34,35 Several reports have highlighted the participation of autophagy regulation in different cancers, including OS. 36,37 In the present study, we showed that miR-193b significantly increases the expression of autophagy-related proteins in OS cells and promotes cell sensitivity to epirubicin treatment, indicating that miR-193b-induced OS cell apoptosis may be autophagy-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…42 Sensitizing GBM cells to temozolomide via regulating autophagy has been widely reported by scholars. [68][69][70][71][72] With respect to the interplay between autophagy and AS, splicing autophagy-related genes has been reported to influence autophagy. 73,74 However, no study has reported the correlation between AS and autophagy in GBM.…”
Section: Discussionmentioning
confidence: 99%